The Role of Teachers in Face-to-Face Learning After the Covid-19 Pandemic to Overcome "Learning Loss" in Elementary Schools: A Case Study at UM Blitar Laboratory Elementary School: Peran Guru dalam Pembelajaran Tatap Muka Pasca Pandemi Covid-19 untuk Mengatasi "Learning Loss" di Sekolah Dasar: Studi Kasus di SD Laboratorium UM Blitar - Septa Hardhita, Rizki; Rahman, Fatchur; Luswandari, Wulan Fatikhah; Handayanto, Supriyono Koes; Kusumaningrum, Shirly Rizki (Pedagogia : Jurnal Pendidikan, 2024)
This study investigates the efficacy of teachers' roles in face-to-face learning to mitigate learning loss post the COVID-19 pandemic, focusing on grade VI at an exemplary elementary school. Employing a descriptive qualitative approach with a case study method, the research involves principals, grade VI teachers, and students. Findings reveal that the teachers' effective implementation of diverse learning media tailored to student needs, consistent application of consequences and rewards, and utilization of a YouTube channel for supplementary learning materials contributed to a significant reduction in learning loss. Notably, the school achieved outstanding literacy and numeracy abilities, ranking among the top nationally. The implications underscore the importance of innovative teaching methods and technology integration in post-pandemic educational recovery efforts. Highlights: Effective teacher roles post-COVID: Diverse teaching media, consistent application of consequences and rewards, utilization of digital platforms like YouTube for supplemental learning. Success factors: Adaptable teaching methods tailored to student needs, proactive use of technology, and maintaining high academic standards. Academic achievements: Notable literacy and numeracy abilities, top-ranking nationally, and successful performance in standardized tests like OSN at the provincial level. Keywords: teacher role, face-to-face learning, learning loss